Impact of Logbooks and Work Plans on Faculty Performance: A Case Study of Private Colleges in Nepal - Bajracharya, Rajan Bilas; Mathema, Bishwas; Adhikari, Ananda (Academia Journal of Research and Innovation, 2026)
Higher education, teaching, and learning have been made more effective through systematic planning, proper documentation, and continuing monitoring of faculty activities. Logbooks and work plans are acknowledged as primary means through which faculty performance is improved by allowing them to be more accountable, better manage their time, and be more aligned with institutional goals. The objective of this research was to understand how the use of logbooks and work plans affects faculty performance in one private college in Nepal. The research employed a descriptive and analytical case study design and integrated both quantitative and qualitative methods. A total of 51 faculty members participated in the study with structured questionnaires, open-ended questions, and a review of faculty logbooks and work plans. For quantitative data, descriptive statistical techniques were used to analyze the data, whereas qualitative responses were subjected to thematic analysis for interpretation. The outcomes indicated that the logbooks and workplans had a positive impact on teaching organization, syllabus alignment, classroom accountability, and reflective practice, which, in turn, contributed to the improvement of timely course completion and classroom management. Despite the positive impact, there were difficulties related to administrative burden, limited training, and weak institutional recognition that at times reduced the effectiveness of these tools. Faculty proposed digitalization, structured feedback, and integration into performance appraisal systems as means to maximize benefits. The study provides realistic insights for the administrators, faculty, and policymakers to enhance the quality of teaching and accountability in private colleges.